Decision and game theory for security Second International Conference, GameSec 2011, College Park, MD, Maryland, USA, November 14-15, 2011. Proceedings - GameSec (Conference) College Park, MD) 2011; Baras, John S.; Katz, Jonathan; Altman, Eitan; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Decision and Game Theory for Security, GameSec 2011, held in College Park, Maryland, USA, in November 2011. The 16 revised full papers and 2 plenary keynotes presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on attacks, adversaries, and game theory, wireless adhoc and sensor networks, network games, security insurance, security and trust in social networks and security investments.
Electronic reproduction.
Keywords: Computer security -- Congresses; Computer networks -- Security measures -- Congresses; Game theory -- Congresses; Electronic books